Effects of Salinity and Mycorrhizal Inoculation (Glomus fasciculatum) on Growth Responses of Grape Rootstocks (Vitis spp.) - Belew, D.; Astatkie, T.; Mokashi, M.N.; Getachew, Y.; Patil, C.P. (South African Journal of Enology and Viticulture, 2016)
A pilot experiment was conducted to determine the effects of soil salinity and inoculation with arbuscular mycorrhizal fungus (Glomus fasciculatum) on growth (shoot length, leaf number, internode length, and total dry weight), spore count and root colonisation of grape rootstocks (Salt Creek, St. George, Dogridge and 1613). Analysis of variance results revealed that increasing salinity reduces growth, spore count and root colonisation, with St. George rootstock showing the highest reduction. Although all rootstocks responded positively to mycorrhizal inoculation, the extent of host preference varied significantly. Dogridge was the least preferred, while the 1613 rootstock was the most preferred. The arbuscular fungal symbiosis increased vegetative growth, with 1613 attaining the highest growth under saline conditions. All the inoculated rootstocks exhibited longer internodes, indicating the beneficial role of mycorrhizal inoculation for improving plant growth and salt tolerance. Based on overall growth and total dry matter accumulation, the salt tolerance ranking of the four rootstocks, in decreasing order, was Dogridge, Salt Creek, 1613 and St. George.